2011
DOI: 10.1111/j.1460-9568.2011.07784.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel form of presynaptic CaMKII-dependent short-term potentiation between Lymnaea neurons

Abstract: Short-term plasticity is thought to form the basis for working memory, the cellular mechanisms of which are the least understood in the nervous system. In this study, using in vitro reconstructed synapses between the identified Lymnaea neuron visceral dorsal 4 (VD4) and left pedal dorsal 1 (LPeD1), we demonstrate a novel form of short-term potentiation (STP) which is 'use'- but not time-dependent, unlike most previously defined forms of short-term synaptic plasticity. Using a triple-cell configuration we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…In view of this, we can speculate that chemically-induced epileptiform activity effectively promotes a short-lasting form of synaptic plasticity in our system. Our observations bear resemblance to a novel form of short-term potentiation described in reconstructed synapses between Lymnaea VD4 and LPeD1 neurons, which exhibit an enhancement of basal transmission with comparable decay kinetics following tetanisation [83]. In both cases, there is an increase in the first EPSP amplitude followed by a rapid depotentiation upon triggering a few action potentials.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In view of this, we can speculate that chemically-induced epileptiform activity effectively promotes a short-lasting form of synaptic plasticity in our system. Our observations bear resemblance to a novel form of short-term potentiation described in reconstructed synapses between Lymnaea VD4 and LPeD1 neurons, which exhibit an enhancement of basal transmission with comparable decay kinetics following tetanisation [83]. In both cases, there is an increase in the first EPSP amplitude followed by a rapid depotentiation upon triggering a few action potentials.…”
Section: Discussionsupporting
confidence: 77%
“…The same synaptic enhancement is displayed when stimulated at different time-points, since we observed that the potentiated response is similar from 15 to 30 minutes following epileptiform activity. On the basis of these properties, these forms of plasticity have been defined as use- rather than time-dependent [83]. A similar use-dependent dynamic upregulation of synaptic transmission has also previously been described in the CA1 area of rat hippocampus [84], thus excluding that these synaptic modulations are restricted to invertebrate neurons.…”
Section: Discussionmentioning
confidence: 93%
“…In mollusks, CaMKII participates in short-term synaptic potentiation [12], intermediate-term sensitization [13] and consolidation of long-term memory (LTM) [14], but its molecular mechanisms are not well understood. In the courtship conditioning in the fruit-fly Drosophila , in which a male fly exposed to a previously mated female exhibits suppression of courtship to a virgin female, inhibition of CaMKII in the central complex and parts of the lateral protocerebrum impairs memory formation [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies implicate presynaptic CaMKII in different forms of synaptic plasticity (25)(26)(27)(28)(29), including modulation of paired-pulse facilitation (30 -32). CaMKII forms a complex with Ca V 2.1 channels in transfected cells via a site in the proximal C-termi-nal domain (33).…”
mentioning
confidence: 99%